Glutamine Metabolism: Molecular Regulation, Biological Functions, and Diseases - Mudasir A. Kumar; Sana Khurshid Baba; Inamu Rashid Khan; Mohd Shahnawaz Khan; Fohad Mabood Husain; Saheem Ahmad; Mohammad Haris; Mayank Singh; Ammira S. Al‐Shabeeb Akil; Muzafar A. Macha; Ajaz A. Bhat (MedComm, 2025)
ABSTRACT Glutaminolysis, the metabolic process of converting glutamine into key intermediates, plays an essential role in cellular energy production, signaling, biosynthesis, and redox balance. Deregulation of glutamine metabolism significantly influences various pathological conditions, including cancers and metabolic and neurological diseases. Emerging evidence shows that long noncoding RNAs (lncRNAs), circular RNAs (circRNAs), and oncogenic alterations in glutamine transporters and enzymes enhance glutamine's role as an alternative energy source, supporting cell survival and proliferation under nutrient and oxygen deprivation conditions. To combat the pathogenic effects of altered glutamine metabolism, researchers are developing targeted inhibitors of key enzymes and transporters involved in glutaminolysis. By interfering with the mechanisms that support the growth of cancer cells, these inhibitors may be able to stop the growth of tumors and treat metabolic and neurological conditions. This review provides a comprehensive overview of existing inhibitors and ongoing clinical trials targeting glutamine metabolism, focusing on its potential as a cancer therapeutic strategy. Additionally, the role of lncRNAs and circRNAs in regulating glutamine metabolism is explored, revealing novel avenues for therapeutic intervention in cancer and other diseases.